Essential Medicines for Children: An Endocrine Perspective - Sanjay Kalra; Yashdeep Gupta (Kerman University of Medical Sciences, 2014)
The emergence of endocrine disease has created significant challenges for healthcare policy-makers and payers across the world. Policy-makers have to ensure availability of drugs used for various endocrinopathies. One way in which this is facilitated is through the World Health Organization (WHO) List of Essential Medicines (LEM). The LEM aims to cover the basic pharmaceutical needs of the majority of people seeking healthcare (1).